2009
DOI: 10.1111/j.1365-2109.2008.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefit of clove oil sedation on animal welfare during salmon smolt,Salmo salarL. transport and transfer to sea

Abstract: The purpose of this study was to determine the e¡ect of clove oil (4.0 mg L À 1 ) sedation, compared with nonsedation, on the primary (plasma cortisol), secondary (osmoregulation) and tertiary (mortality) stress responses in Atlantic salmon smolts during transport and transfer to sea. Clove oil sedation during on-and o¡-loading su⁄ciently reduced the primary stress response to lower mortality (2.1%) during transfer to sea compared with unsedated ¢sh, which experienced a mortality rate above 12.2%. The unsedate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 57 publications
1
44
0
1
Order By: Relevance
“…This seemed to be supported by the fact that secondary and tertiary stress responses as plasma chloride, magnesium, fin rot and mortality, were significantly increased in the "stress and vaccine" group compared to the "vaccine and stress" and the control group. Earlier studies have shown that cortisol is often associated with the detrimental effects of stress including: decreased growth rates, reproductive dysfunction (Morgan et al 1999;Schreck et al 2001;Mommsen et al 1999), increased incidence of disease (Barton 2002;Davis et al 2002Davis et al , 2003Einarsdottir et al 2000a;Einarsdottir et al 2000b;Weyts et al 1999), reduced seawater tolerance (Ventura et al 2011;Iversen et al 2009;Mommsen et al 1999;Redding and Schreck 1983;Sandodden et al 2001) and survival (Iversen et al 2005;Portz et al 2006;Finstad et al 2003;Iversen et al 1998;Hasan and Bart 2007). It has also been suggested that if the fish is not permitted enough time to recover completely after stress, a second, normally nonfatal, stressful occurrence could be fatal (Carmichael 1984), as observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This seemed to be supported by the fact that secondary and tertiary stress responses as plasma chloride, magnesium, fin rot and mortality, were significantly increased in the "stress and vaccine" group compared to the "vaccine and stress" and the control group. Earlier studies have shown that cortisol is often associated with the detrimental effects of stress including: decreased growth rates, reproductive dysfunction (Morgan et al 1999;Schreck et al 2001;Mommsen et al 1999), increased incidence of disease (Barton 2002;Davis et al 2002Davis et al , 2003Einarsdottir et al 2000a;Einarsdottir et al 2000b;Weyts et al 1999), reduced seawater tolerance (Ventura et al 2011;Iversen et al 2009;Mommsen et al 1999;Redding and Schreck 1983;Sandodden et al 2001) and survival (Iversen et al 2005;Portz et al 2006;Finstad et al 2003;Iversen et al 1998;Hasan and Bart 2007). It has also been suggested that if the fish is not permitted enough time to recover completely after stress, a second, normally nonfatal, stressful occurrence could be fatal (Carmichael 1984), as observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mortality was not lower with the use of EO-O, on the contrary, fish transported with the higher concentration of EO in SW had significantly higher mortality than the other groups. Several studies have shown that sedation can decrease post-transport mortality (Inoue et al, 2005;Iversen et al, 2009;Pramod et al, 2010). However, in this study an increase of mortality after transport was detected at 30 µl/L EO-O.…”
Section: Eo-y (µL Lmentioning
confidence: 99%
“…This practice inevitably involves stress and may cause a large-scale mortality. Several studies have shown the positive effect of anesthetics during transport of many fish species (Inoue et al, 2005;Iversen et al, 2009;Pramod et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Animals transported with eugenol had significantly lower plasma cortisol levels (Inoue et al, 2005). During transportation of salmon, higher values of plasma cortisol were observed in the control group compared to eugenol (Iversen et al, 2009). In the same study, higher plasma cortisol concentrations were found in benzocaine-exposed fish as compared to those exposed to eugenol (Iversen et al, 2003).…”
Section: Discussionmentioning
confidence: 90%